Changes in the organs and tissues of the oral cavity in the new coronavirus infection (COVID-19): A review - Dmitry I. Trukhan; Anatoly F. Sulimov; Larissa Yu. Trukhan (ZAO "Consilium Medicum", 2022)
SARS-CoV-2 infection can cause changes in the organs and tissues of the oral cavity, which is associated with a wide distribution of angiotensin-converting enzyme type 2 in the oral cavity, mainly epithelial cells of the oral mucosa, gums and fibroblasts of the periodontal ligament. Thus, the oral mucosa is susceptible to SARS-CoV-2 infection and may act as a gateway for the virus, as well as a reservoir for SARS-CoV-2. We searched the literature for the period from the beginning of the pandemic until May 30, 2022, devoted to the study of changes in the organs and tissues of the oral cavity with a new coronavirus infection (COVID-19) in the electronic search engines PubMed/MEDLINE and Scopus. A special place in the study of changes in the organs and tissues of the oral cavity with a new coronavirus infection (COVID-19) is occupied by periodontal pathology. A number of reviews and clinical studies conclude the importance of good oral hygiene and periodontal health as an important aspect of COVID-19 prevention and management. Oral probiotics can be considered as a promising direction for correcting changes in organs and tissues of the oral cavity in COVID-19.